Global Trend on Logistics Research: A Bibliometric - Habibullah, Habibulllah; Pudjianto, Bambang (Asian Journal of Logistics Management, 2022)
This study uses bibliometric analysis, visualization, and VOS viewer application, which is based on the Scopus document database, to assess the research journals on logistics. The Study used 1,000 papers on logistics-related themes from foreign authors. A number of factors are used to evaluate articles, including contributions from a country, an institution, an author, journal distribution, the most-cited articles, bibliographic coupling, and keyword analysis. The results showed that the first article indexed by Scopus, which discussed logistics, was published in 1984. Marija Bogataj from the Faculty of Economics, University of Ljubljana, Slovenia, is the most productive author, with nine articles discussing logistics. The United States is the country that produces the most articles on the theme of logistics, namely 194 articles, and Indonesia is ranked 11th. Hong Kong Polytechnic University is an institution that is the primary reference in research on logistics. The International Journal of Production Economics is the most published in logistics research. Potential logistics research themes include blockchain, outsourcing, gender, poverty, coordination, supply chain strategy, packaging, circular economy, and urban logistics. Research is carried out by collaborating across disciplines and countries to make a real contribution to research, education, and the logistics industry.